ANTIFUNGAL ACTIVITY OF NATURAL COLOURANT FROM MELIA COMPOSITA BARK AND ITS APPLICATION IN FUNCTIONAL TEXTILE FINISHING - Pal, Anita; Kumar, Rakesh; Tripathi, Y. C. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The present study was aimed to evaluate the antifungal efficacy of natural dye obtained from Melia composita bark and its impact on the antimicrobial finishing of different types of textile fabrics. Methods: Antifungal activity of M. composita bark dye was assessed against standard strains of five fungi namely Aspergillus flavus, A. niger, A. parasiticus, Fusarium moniliforme and Penicillium canescens using agar-well diffusion method. The minimum inhibitory concentration (MIC) was determined by broth dilution method. The antifungal potency of dyed fabrics (silk, wool, and cotton) against the five test fungi was quantitatively evaluated by reported method. Results: Different treatment doses of natural dye exhibited a varying degree of antifungal activity against the five test fungi. The treatment dose of 100 mg/ml and above were considerably active. Growth inhibition impact of natural dye at 250 mg/ml dose was almost at par with positive control. Maximum growth inhibition in all the five test fungi was evident with 500 mg/ml dose followed by 250 and 100 mg/ml. MIC of the natural dye against test fungi were found in the range of 20.50-23.00 mg/ml. Dyed fabrics of silk, wool, and cotton also showed remarkable antifungal efficacy against all the test fungi. The highest growth reduction was observed in A. parasiticus whereas lowest in P. canescens with the three types of dyed fabrics. Dyed wool fabrics exhibited the maximum growth reduction followed by silk and cotton fabrics. Conclusion: The study revealed the remarkable antifungal activity of natural dye from barks of M. composita; therefore, the plant can be considered as a good source of natural dye with functional properties and can be used in commercial dyeing and protective finishing of different kinds of textile fabrics. Keywords: Melia composita, Bark, Natural Dye, Dyed Fabrics, Antifungal activity Â 